2021
DOI: 10.48550/arxiv.2110.03095
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Which Shortcut Cues Will DNNs Choose? A Study from the Parameter-Space Perspective

Abstract: Deep neural networks (DNNs) often rely on easy-to-learn discriminatory features, or cues, that are not necessarily essential to the problem at hand. For example, ducks in an image may be recognized based on their typical background scenery, such as lakes or streams. This phenomenon, also known as shortcut learning, is emerging as a key limitation of the current generation of machine learning models. In this work, we introduce a set of experiments to deepen our understanding of shortcut learning and its implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Shah et al [87] show empirically that in certain scenarios neural networks can suffer from extreme simplicity bias and rely on simple spurious features, while ignoring the core features; in Section 4.2 we revisit these problems and provide further discussion. Hermann and Lampinen [38] and Jacobsen et al [45] also show synthetic and natural examples, where neural networks ignore relevant features, and Scimeca et al [86] explore which types of shortcuts are more likely to be learned. Kolesnikov and Lampert [50] on the other hand show that on realistic datasets core and spurious features can often be distinguished from the latent representations learned by a neural network in the context of object localization.…”
Section: Related Workmentioning
confidence: 99%
“…Shah et al [87] show empirically that in certain scenarios neural networks can suffer from extreme simplicity bias and rely on simple spurious features, while ignoring the core features; in Section 4.2 we revisit these problems and provide further discussion. Hermann and Lampinen [38] and Jacobsen et al [45] also show synthetic and natural examples, where neural networks ignore relevant features, and Scimeca et al [86] explore which types of shortcuts are more likely to be learned. Kolesnikov and Lampert [50] on the other hand show that on realistic datasets core and spurious features can often be distinguished from the latent representations learned by a neural network in the context of object localization.…”
Section: Related Workmentioning
confidence: 99%
“…While the distribution shift explains part of the story, we emphasize that what is equally important for shortcut learning is the difficulty of the spurious features themselves (see Fig- 1). Previous works like Shah et al (2020); Scimeca et al (2021) hint at this. But we take this line of thought further by viewing shortcut learning as a phenomenon that impacts the dataset difficulty, which can be captured by monitoring early training dynamics.…”
Section: Introductionmentioning
confidence: 75%
“…Rather only those spurious features that are easier than the core features are potential shortcuts (see Fig- 1). Previous works like Shah et al (2020); Scimeca et al (2021) hint at this by saying that DNNs are biased towards simple solutions, and Dagaev et al (2021) use the "too-good-to-be-true" prior to emphasize that simple solutions are unlikely to be valid across contexts. Veitch et al (2021) distinguish various model features using tools from causality and stress test the models for counterfactual invariance.…”
Section: Related Workmentioning
confidence: 99%
“…Biases in machine learning. Emerging studies on DNNs have revealed that DNNs rely on shortcut biases [4,10,21,22,44]. The existing de-biasing methods let a model less attend on the dataset biases in an implicit way by using extra biased networks [4,10] or data augmentations [22] without using bias labels.…”
Section: Related Workmentioning
confidence: 99%